Mapping Innovation Systems in Latin America: a bibliometric review of current trends (2022)
Innovation Systems (IS) is a context-specific topic that still presents a challenge to emerging countries. In this perspective, the present study aims to provide a map of current publications regarding Innovation Systems in the context of Latin America. Data shows Brazil is the current leader in publications on the topic, followed by Colombia and Mexico. Innovation systems relations and sectoral innovation systems - agriculture, health, food, and education - are the main focus, while sustainability and other relevant sectors lack proper attention. Challenges and best practices in SMEs regarding its interaction with IS are also key aspects as this type of organization represents around 99% of the companies in this region.